Efect of fque fibers and its processing by‑products on morphology, thermal and mechanical properties of epoxy based biocomposites (2022)
This work examines the morphology, mechanical and thermal properties of biocomposites based on epoxy resin-EP and fque (Furcraea andina), a native crop of South America. The EP-fque biocomposites were prepared using fque powder-FP an industrial waste generated during fque processing, nonwoven fque fber mats-NWF and unidirectional fque fber mats-UF oriented at 0° and 90°. The addition of fque into EP matrix restricts EP macromolecule chains movement and enhance the thermal stability of EP. SEM images showed that fque form used (powder or fber) and matarrangement can generate changes in the biocomposites morphology. Mechanical characterization show that fque powder and fque fbers oriented at 90° acts as fllers for the epoxy matrix while the fque fbers oriented at 0° reinforce EP matrix increasing the tensile and fexural modulus up to 5700 and 1100% respectively and tensile and fexural strength up to 277% and 820% in comparison with neat EP. The obtained results can increase the interest in researching and developing products from fque Powders and other natural fbers processing byproducts thus reducing the abundance of waste in soil and landflls and environmental concerns and suggest that the EP-fque biocomposites are promising to be used in the automotive sector